European approach to assess the fire performance of façades. (22nd June 2020) - Anderson, Johan; Boström, Lars; Chiva, Roman; Guillaume, Eric; Colwell, Sarah; Hofmann, Anja; Tóth, Péter
SUMMARY: Several attempts have been made in the past to develop a European harmonized testing and assessment method for façades before the European commission decided to publish a call for tender on the topic. A project consortium from five countries (Sweden, UK, France, Germany and Hungary) applied to the call for tender and was contracted to develop a European approach to assess the fire performance of façades. 24 sub‐contractors and 14 stakeholder entities were part of the project. The objective of the European project was to address a request from the Standing Committee of Construction (SCC) to provide EC Member States regulators with a means to regulate the fire performance of façade systems based on a European approach agreed by SCC. The initial stages of this project were focused on establishing a register of the regulatory requirements in all Member States in relation to the fire performance of façade systems, and to identify those Member States who have regulatory requirements for the fire performance façade systems which go beyond the current EN 13501 (reaction to fire and fire resistance) classification systems and to collate the details of these additional requirements. After having confirmed the regulatory needs a testing and classification methodology based on BS 8414 and DIN 4102‐20 was developed to address the identified key performance and classification characteristics. This paper is a short overview of results the two‐year development work, which Final Report published by the European Commission in 2018.